Telaah Konsep Kecerdasan Spiritual Anak Jalaluddin Rahmat - Azizunisak Hidayati Wahyuna; Moh. Toriqul Chaer (Program Studi PGRA, 2020)
Jalaluddin Rakhmat is known as a prolific scholar. He has produced over forty books. One of his talk about the importance of education based on spiritual intelligence in children. Jalaluddin Rakhmat according to children born with high spiritual intelligence, but parental treatment and the environment that causes children sometimes lose spiritual potential. This study uses the approach to study a text. The text to be the focus of this study is the concept of spiritual intelligence expressed Jalaluddin Rakhmat. Results of the study found three important points with regard to the concept of spiritual intelligence-based education of the child, namely: (1) maximization of existing influence body against soul, (2) maximization of existing influence soul of psychophysical and psychosocial, and (3) guidance towards mystical experience.